Enhanced weathering potentials—the role of in situ CO2 and grain size distribution - Amann, Thorben; Hartmann, Jens; Hellmann, Roland; Pedrosa, Elisabete Trindade; Malik, Aman (Frontiers in Climate, 2022)
The application of rock powder on agricultural land to ameliorate soils and to remove carbon dioxide from air by chemical weathering is still subject to many uncertainties. To elucidate the effects of grain size distribution and soil pCO2 levels on CO2 uptake rates, two simple column experiments were designed and filled nearly daily with an amount of water that simulates humid tropical conditions, which prevail in areas known for being hotspots of weathering. Multiple materials (dunite, basanite, oxisol, a combination of the latter two, and loess) were compared under ambient and 100% CO2 atmosphere. In a second series, single material columns (dunite) were filled with three different grain size distributions. Total alkalinity, pH, major ions, and dissolved silica were determined in the outflow water of the columns for about 300 days. Under ambient atmospheric conditions, the CO2 consumption was lowest in the oxisol column, with 100 t CO2 km-2 yr-1, while dunite and basanite showed similar consumption rates (around 220 t CO2 km-2 yr-1). The values are comparable to high literature values for ultramafic lithologies. Interestingly, the mixture of basanite and oxisol has a much higher consumption rate (around 430 t CO2 km-2 yr-1) than the basanite alone. The weathering fluxes under saturated CO2 conditions are about four times higher in all columns, except the dunite column, where fluxes are increased by a factor of more than eleven. Grain size distribution differences also play a role, with highest grain surface area normalized weathering rates observed in the columns with coarser grains, which at first seems counterintuitive. Our findings point to some important issues to be considered in future experiments and a potential rollout as a carbon dioxide removal method. Only in theory do small grain sizes of the spread-material yield higher CO2 drawdown potentials than coarser material. The hydrologic conditions, which determine the residence times in the pore space, i.e., the time available for weathering reactions, can be more important than a small grain size. Saturated-CO2 column results provide an upper limit for weathering rates under elevated CO2.